Analiza finansowa w jednostkach samorządu terytorialnego na przykładzie Miasta i Gminy Środa Wlkp - Mrówczyńska-Kamińska, Aldona; Kucharczyk, Anna; Średzińska, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of an article is a presentation of analysis of a city and a district of Środa Wlkp financial situation, as a local government unit. The local unit analysis concerns on budget data as a base for a rational use of possessed sources. It is especially important for local government unit performance because of strengthen demand for increasing effectiveness in relation to fulfilling needs of a local community and to develop local government unit performance. The budget should be treated as a standard act, as well as a instrument of an effective and rational financial management in local government units. The effective style of management in local unit, especially in finance sphere, should concern on a rational usage of the most suitable methods like financial analysis mainly.